Handbook Utility Management - Bausch, Andreas; Schwenker, Burkhard (Springer Berlin Heidelberg : Imprint: Springer, 2009)
As the deregulation of European utility markets has progressed, the dynamics of and the competitive pressure in the utility industries have steadily intensified over recent years. These changes in the regulatory framework have caused a shift in the direction of an integrated market environment, resulting in new challenges for the management of power and gas companies and a substantial need for strategic reorientation. The Handbook Utility Management is concerned with these changes and challenges in the utility industries and emerging managerial issues of high practical relevance. Inclusion of the latest insights into the economic, technological, and legal drivers of the diverse value chain activities makes the Handbook a valuable asset for both professionals and researchers.